2023
DOI: 10.3390/diagnostics13040591
|View full text |Cite
|
Sign up to set email alerts
|

Preanalytical Errors in a Hematology Laboratory: An Experience from a Tertiary Care Center

Abstract: Background: Laboratory errors arise at any stage of testing. Detecting these inaccuracies before results are revealed might delay diagnosis and treatment, causing patient distress. Here, we studied the preanalytical errors in a hematology laboratory. Methods: This one-year retrospective analysis was conducted at the laboratory of a tertiary care hospital and included information on blood samples that were taken for hematology tests from both outpatients and inpatients. Laboratory records included sample collec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…In this study, we also discovered another type of preanalytical error (clotted specimen), which accounts for 1.9 % of all errors. This finding is lower than the findings of research conducted in Oromia, Ethiopia, 21.9 % [ 25 ]; Saudi Arabia, 20.09 % [ 20 ]; Cantonal Hospital Zenica in Bosnia and Herzegovina, 39.87 % [ 19 ]; and Libya, 25 % [ 23 ] of specimens were rejected due to the occurrence of the clot. A study conducted in Saudi Arabia [ 14 ], however, found a lower proportion, i.e., 0.08 % specimen rejection rate due to the clotting of specimens.…”
Section: Discussionmentioning
confidence: 61%
See 2 more Smart Citations
“…In this study, we also discovered another type of preanalytical error (clotted specimen), which accounts for 1.9 % of all errors. This finding is lower than the findings of research conducted in Oromia, Ethiopia, 21.9 % [ 25 ]; Saudi Arabia, 20.09 % [ 20 ]; Cantonal Hospital Zenica in Bosnia and Herzegovina, 39.87 % [ 19 ]; and Libya, 25 % [ 23 ] of specimens were rejected due to the occurrence of the clot. A study conducted in Saudi Arabia [ 14 ], however, found a lower proportion, i.e., 0.08 % specimen rejection rate due to the clotting of specimens.…”
Section: Discussionmentioning
confidence: 61%
“…Of the total specimens collected the overall specimen rejection rate found in the current study is similar to the overall specimen rejection rates obtained from studies done at the University of Gondar Hospital, Northwest Ethiopia, 3.8 % [ 15 ]; in Zimbabwe, 4 % [ 16 ], and Nepal, 5.5 % [ 17 ]. However, the overall sample rejection at the pre-analytical phase in the current study is higher than the studies conducted at Amhara Public Health Institute in Bahir Dar, Ethiopia, 0.5 % [ 9 ]; St. Paul's Hospital Millennium Medical College in Addis Ababa, Ethiopia, 1.4 % [ 1 ]; Delhi, 1.52 % [ 18 ]; Cantonal Hospital Zenica, 1.7 % [ 19 ]; and Makkah, Saudi Arabia, 1.3 % [ 20 ]. On the other hand, our study's finding indicates a lower rate of overall sample rejection in the pre-analytical phase compared to the rate of overall pre-analytical sample rejection of previous studies conducted at St. Paul's Hospital Millennium Medical College in Addis Ababa, Ethiopia,26 % [ 2 ]; St. Paul's Hospital Millennium Medical College (SPHMMC) in Addis Ababa, Ethiopia,72.3 % [ 21 ], and Saudi Arabia, 12.1 % [ 14 ].…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…Recent studies have shown the relationship of fluid overload with adverse outcomes; hence, manage and optimization of fluid balance becomes a central component of the management of critically ill patients [5,6]. Acute myeloid leukaemia (AML) is a condition in which myeloblast count rapidly increase in bone marrow, so normal functioning erythrocyte precursors are decreased in number resulting in reduced blood cell count.…”
Section: Discussionmentioning
confidence: 99%
“…Different pre-analytical errors hamper the accuracy of laboratory results: sample clotting, insufficient volume of blood in a test tube, diluted sample, haemolysis, wrong test tube for an intended test, wrong identification label on a test tube, etc. [1,2]. There were no symptoms of acute bleeding.…”
mentioning
confidence: 93%